Case report: IgG4-related mass-forming thyroiditis accompanied by regional lymphadenopathy - Yasuhiro Sakai; Yoshiaki Imamura (BMC, 2018)
Abstract Background It has been recently accepted that IgG4-related thyroiditis is comparable to the Hashimoto and Riedel thyroiditis and Graves disease which are rich in IgG4-secreting plasma cells. Many physicians believe that in IgG4-related thyroiditis, the thyroid is entirely enlarged and diffusely affected, which is similar to conventional thyroiditis, but rarely ever accompanied by pseudoneoplastic mass formation as in IgG4-related disease in the other organs. This report introduces another pattern of IgG4-related thyroiditis as mass-forming thyroiditis and presents the occurrence of IgG4-related regional lymphadenopathy as an unusual accompanying symptom. Case presentation A 66-year-old woman presented with an approximately 2.5-cm mass in the right thyroidal lobe and regional lymph node swelling, which were preoperatively misinterpreted as thyroidal carcinoma. After lobectomy, histological examination was performed, revealing that the mass showed dense stromal fibrosis, lymphoplasmacytic infiltration, and effacement of thyroid follicles, while the background thyroidal tissue seemed to mimic lymphocytic thyroiditis without fibrosis. Immunohistochemistry revealed predominance of IgG4-secreting plasma cells among infiltrating lymphocytes independent of mass lesion or background tissue. In addition, the regional Delphian and paratracheal lymph nodes were swollen, histologically showing numerous IgG4-secreting plasma cell infiltrations in the interfollicular zone. Conclusions IgG4-related mass-forming thyroiditis, which may be an extremely rare but recognizable pattern of IgG4-related thyroiditis, may be distinguishable from Hashimoto and Riedel thyroiditis, Graves disease, and thyroidal carcinoma. In addition, the regional IgG4-related lymphadenopathy, also possibly misdiagnosed as metastatic thyroidal carcinoma, may be a newly recognized manifestation of IgG4-related thyroiditis.